Determinants of Problem Drinking and Depression among Latino Day Laborers. (3rd July 2014) - Bacio, Guadalupe; Moore, Alison; Karno, Mitchell; Ray, Lara
Abstract : Little is known about alcohol misuse and depression among Latino day laborers despite the fact that they encounter multiple stressors (e.g., job instability, unsafe work environments). A structural equation model tested the relationships among laborer stress, social support, health status, current alcohol misuse, and depression. A sample of 89 male, urban Latino day laborers completed measures assessing these constructs in 2011. Stress was negatively related to physical health status, which was associated with depression. Findings suggest that stressors specific to being a day laborer resulting from their work and living conditions generate and maintain health disparities in this vulnerable population.